IDEF0-Technology of Modeling of Processes of Minimization the Resistance of the Personnel to Organizational Changes at the Enterprise - Stashkevych, I. I.; Turlakova, S. S.; Shevchenko, O.; Derzhevetska, M. A.; Турлакова, С. С.; Держевецька, М. А. (University of Naples "Federico II", 2020)
The structural and functional IDEF0-model of information support of processes of minimization of resistance of the personnel to organizational changes at the enterprise is developed. The proposed model makes it possible to describe in a logical, convenient and consistent form therelationship between management functions and responsible executives, provides information about resources, information flows, instructions, regulatory information, a set of models and approaches. The corresponding model in the notation IDEF0 will provide information support for decision-makingon the management of organizational changes at the enterprise.
Keywords: information interaction; personnel; decision support; information modeling; structural and functional model; IDEF0-model; enterprise